2018
DOI: 10.22543/7674.51.p4652
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor disorders in gynecological malignancies. An overlooked problem?

Abstract: Cervical, endometrial, ovarian, vulvar, and vaginal cancers affect women of a broad age spectrum. Many of these women are still sexually active when their cancer is diagnosed. Treatment options for gynecological malignancies, such as gynecological surgery, radiation, and chemotherapy, are proven risk factors for pelvic floor dysfunction. The prevalence of urinary incontinence, fecal incontinence, and sexual dysfunction before cancer treatment is still unclear. Hypotheses have been raised in the literature that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In our case, the hypothesis of chemotherapy induced non-melanoma skin cancer rose. However, in a case-control clinical trial by Rubino et al, no association was found between chemotherapy and non-melanoma skin cancer (14). The possibility that adjuvant chemotherapy influenced the aetiology of the skin cancer, in this case, is therefore low.…”
Section: Discussionmentioning
confidence: 67%
“…In our case, the hypothesis of chemotherapy induced non-melanoma skin cancer rose. However, in a case-control clinical trial by Rubino et al, no association was found between chemotherapy and non-melanoma skin cancer (14). The possibility that adjuvant chemotherapy influenced the aetiology of the skin cancer, in this case, is therefore low.…”
Section: Discussionmentioning
confidence: 67%
“…The case that we reported presented a tumour size of more than 2 cm and it had grown more than 1 mm (0.04 inches) into underlying tissue (stroma) (T1b), no spread to the regional lymph nodes (N0) with no distant metastasis (M0) that was classified as stage IB according to AJCC and FIGO classifications. 6,32 In our case radical vulvectomy was necessary considering the tumour size. Separate incisions were given for inguinal lymphadenectomy, hence the triple butterfly incision.…”
Section: Discussionmentioning
confidence: 76%
“…The information required are the dimension and extent of the tumour, node status and presence of distant metastasis. The case that we reported presented a tumour less of 5 cm with invasion in the vulva and lower urethra (T2), spread in 4 regional lymph nodes (N2b) with no distant metastasis that was classified as stage IIIb according to AJCC and FIGO classifications (1,10).…”
Section: Discussionmentioning
confidence: 95%